6-Gingerol Normalizes the Expression of Biomarkers Related to Hypertension via PPARδ in HUVECs, HEK293, and Differentiated 3T3-L1 Cells. (16th December 2018) - Lee, Yong-Jik; Jang, Yoo-Na; Han, Yoon-Mi; Kim, Hyun-Min; Seo, Hong Seog
Abstract : Hypertension is a disease with a high prevalence and high mortality rates worldwide. In addition, various factors, such as genetic predisposition, lifestyle factors, and the abnormality of organs related to blood pressure, are involved in the development of hypertension. However, at present, there are few available drugs for hypertension that do not induce side effects. Although the therapeutic effects of ginger on hypertension are well established, the precise mechanism has not been elucidated. Therefore, this study was designed to evaluate the antihypertensive mechanism of 6-gingerol, one of the main ingredients of ginger, and to assist in the development of new drugs for hypertension without side effects. The antihypertensive effects and mechanism of 6-gingerol were identified through reverse transcription polymerase chain reaction (RT-PCR), western blotting, and immunocytochemical staining for biomarkers involved in hypertension in human umbilical vein endothelial cells (HUVECs), human embryonal kidney cells (HEK293 cells), and mouse preadipocytes (3T3-L1 cells). The lipid accumulation in differentiated 3T3-L1 cells was evaluated by using Oil Red O staining. 6- Gingerol increased the level of phosphorylated endothelial nitric oxide synthase (eNOS) protein but decreased that of vascular cell adhesion protein 1 (VCAM1) and tumor necrosis factor alpha (TNF α ) in HUVECs. In HEK293 cells, the expression of the epithelial sodium channel (ENaC) protein was reduced by 6-gingerol. Lipid accumulation was attenuated by 6-gingerol treatment in differentiated 3T3-L1 cells. These effects were regulated via peroxisome proliferator-activated receptor delta (PPAR δ ). 6-Gingerol ameliorated the expression of biomarkers involved in the development of hypertension through PPAR δ in HUVECs, HEK293, and differentiated 3T3-L1 cells.